Screen Time and Executive Function in Toddlerhood: A Longitudinal Study - McHarg, Gabrielle; Ribner, Andrew D.; Devine, Rory T.; Hughes, Claire (Frontiers in Psychology, 2020)
Technology is pervasive in homes with young children. Emerging evidence that electronic screen-based media use has adverse effects on executive functions may help explain negative relations between media use and early academic skills. However, longitudinal investigations are needed to test this idea. In a sample of 193 British toddlers tracked from age two to three years, we test concurrent and predictive relations between screen use and children’s executive function. We find no concurrent association between screen use and executive function; however, screen time at age 2 is negatively associated with the development of executive functions in toddlerhood from age 2 to age 3, controlling for a range of covariates including verbal ability. Implications for parenting, education, and pediatric recommendations are discussed.